1996
DOI: 10.1029/96ja01638
|View full text |Cite
|
Sign up to set email alerts
|

A low‐dimensional energy‐conserving state space model for substorm dynamics

Abstract: A low‐ (four‐) dimensional state space model for the basic energy components of the night‐side magnetosphere is developed based on truncated descriptions of the collisionless microscopic (Hamiltonian) energy transfer processes occurring in the quasi‐neutral layer. The substorm trigger, due to bifurcation of the system either from magnetic reconnection or from ballooning‐mirror modes, is modeled by a fast unloading above a critical current. For constant southward interplanetary magnetic field solar wind input, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 37 publications
3
66
0
Order By: Relevance
“…Blanchard et al (1996) estimated a coupling efficiency between the solar wind and the magnetotail reconnection electric field to be 0.1, which is similar to what has been assumed by some modelers (e.g. Horton and Doxas, 1996). Blanchard et al (1996) also reported a peak correlation lagging the solar wind electric field by about 70 min.…”
Section: Discussionsupporting
confidence: 58%
“…Blanchard et al (1996) estimated a coupling efficiency between the solar wind and the magnetotail reconnection electric field to be 0.1, which is similar to what has been assumed by some modelers (e.g. Horton and Doxas, 1996). Blanchard et al (1996) also reported a peak correlation lagging the solar wind electric field by about 70 min.…”
Section: Discussionsupporting
confidence: 58%
“…The analogy was developed into a simplified magnetospheric model by estimating the large-scale electrical properties of the M-I system and combining these electrical components into a driven nonlinear oscillator circuit model (Klimas et al, 1992). It has been further developed into a plasma physics model by Horton and Doxas (1996). In the case of a dissipative, driven, autonomous low dimensional system such as the Lorenz model, the dynamics, rather than exploring all of phase space ergodically, collapses onto a low dimensional region called an attractor.…”
Section: Nonlinear Deterministic Modelsmentioning
confidence: 99%
“…We define a type III substorm as one that is well described by a linear second order filter (LRC filter) with parameters that are within a range of estimates based on magnetospheric scales (Weimer, 1994;Horton and Doxas, 1996). The WINDMI model with no triggering can be reduced to a model with a response function near that of a LRC filter.…”
Section: Type IIImentioning
confidence: 99%
“…which is due to plasma convection, arises from the divergence of the ion off-diagonal momentum stress tensor π (Horton and Doxas, 1996). The closure of the I 1 current loop subtracts from these dusk-to-dawn currents flowing from in regions obtained by mapping the auroral field lines to the geotail.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation